Internet addiction in high school students: prevalence and correlations - Botelho Brito, Alexandre; Miranda Lourenço de Freitas2, Wesley; Guimarães Cunha, Débora; Dias Pires Brito, Kewla; Brito Messias, Romerson; Pinho, Lucineia; Fernanda Santos Figueiredo Brito, Maria; Fagundes Silveira, Marise (Revista Unimontes Científica, 2020)
Objective: to investigate the prevalence of Internet addiction among high school students in Montes Claros-MG and the associated Internet usage profile. Methodology: This is a quantitative, analytical and cross-sectional study of a sample of 966 high school students, both public and private. A questionnaire was applied that includes socio-demographic variables, training and Internet usage profile, as well as Internet Addiction Test. The Pearson correlation coefficient was used to test the linear correlation between the characteristics of use and internet addiction, at a statistical significance of 5% (p <0.05). This study was conducted within the standards of the Helsinki Declaration and approved by the Research Ethics Committee under Protocol # 1,520,173 / 2016. Results: The prevalence of addiction was 9.8%, correlated with type of institution (p = 0.005), daily frequency of internet use (p = 0.001), number of days of weekly use (p = 0.014), number of hours of use on weekends and holidays (p = 0.041) and use at night (p = 0.004). No correlation was found to access online games, to perform school activities or for professional purposes, but was found with access to social networks (p = 0,000), e-mails (p = 0,033) and with the purpose of watching movies, music and videos (p = 0,014). Addicted users also demonstrated an awareness of addiction / addictive behavior (p = 0.000). Conclusion: It was concluded that addiction is associated with habits of Internet use and that they are aware of their addiction. Resumo: Objetivo: investigar a prevalência de adicção em internet dos estudantes secundaristas de Montes Claros-MG e o perfil de utilização da internet associados. Metodologia: Trata-se de um estudo quantitativo, analítico e transversal em uma amostra de 966 alunos do ensino médio público e privado. Foi aplicado um questionário que contempla variáveis sociodemográficas, de formação e de perfil de utilização da internet, além do Internet Addiction Test. O coeficiente de correlação de Pearson foi usado para testar a correlação linear entre as características de utilização e a adicção em internet, a uma significância estatística de 5% (p<0,05). Este estudo foi conduzido dentro dos padrões da declaração de Helsinki e aprovado pelo Comitê de Ética em Pesquisa sob protocolo nº 1.520.173/2016. Resultados: A prevalência de adicção encontrada foi de 9,8%, correlacionada com o tipo de instituição (p= 0,005), frequência diária de uso da internet (p=0,001), número de dias de uso semanal (p=0,014), número de horas de utilização em fins de semana e feriados (p=0,041) e utilização no período noturno (p= 0,004). Não foi encontrada correlação ao acesso para ver jogos online, realizar atividades escolares ou com finalidade profissional, mas foi encontrada com o acesso a redes sociais (p=0,000), e-mails (p=0,033) e com o objetivo de ver filmes, músicas e vídeos (p=0,014). Os usuários adictos demonstraram ainda ter ciência do comportamento adicto/viciante (p= 0,000). Conclusão: Concluiu-se que a adicção está associada com hábitos de utilização da internet e que os mesmos têm consciência da sua adicção.